Library and Information Management and Librarianship in Election Manifestos of Turkey’s Parliamentary Elections on June 07, 2015 - Coşkun Polat; Mehmet Ali Akkaya; Kasım Binici (Türk Kütüphaneciliği)
In this study, it has been evaluated the election manifestos that prepared by political parties for Turkey’s General Elections were held on June 07, 2015 in terms of information and document management discipline. The scope of the study is limited to parties that won the most votes and the right to representation in parliament. Results are produced based on the findings and some suggestions are given for information and records management professionals.